GŁÓWNE PROBLEMY NORMALIZACJI POLSZCZYZNY XVII WIEKU - PIHAN-KIJASOWA, ALICJA; MOTYL, AGNIESZKA (Slavia Occidentalis, 2020)
Research into the literary Polish language of the 17th century was undertaken relatively late. No significant relevant attempts had been made before the mid-20th century. The first detailed studies were made in the 1950s while the 1970s marked significantly advanced studies on the subject. The first monograph of the 17th century Polish language was published as late as in 2002. However, the monograph, presenting the entire grammar system together with the spelling rules and phonetics, does not conclude research into this period as it is rather general and fails to discuss many major issues related to the language’s evolution, for example the regional conditionings of the course of the normalization processes. This is a shortage plaguing many works on the 17th century Polish language. Therefore, it is very difficult to reconstruct the emergence and geographic distribution of linguistic innovations, over time transferring into a language norm. As for the 17th century, we can only refer to the text norm (or a practical norm/usus). In the century in question, a codified (theoretical) norm had not yet been developed although the grammar instructions from that time include some guidelines on linguistic correctness. As printing had already been well developed, we have enough sources to reconstruct text norms and to show its evolution. By referring to studies and text overviews one may conclude that the 17th century inherited from the 16th century a system largely normalized on various levels: the spelling, phonetics and morphology. On the other hand, it also either inherited or produced co-functional variants which only aspired to becoming a part of the norm. On the basis of selected issues from the realm of phonetics, declension and conjugation, the article shows examples of norms inherited from the previous century and, more importantly, processes of new linguistic norms emerging in the 17th century. These processes have been presented not only in reference to the averaged status in the general Polish language but also, whenever possible, their course is presented in the regional varieties of the language. By resorting to the methodology and terminology developed by Irena Bajerowa, the authors have touched upon the issue of the regionally diversified rate of the normalization processes. However, with reference to the 17th century, we are not able to present many linguistic facts in this specific way. What we need is detailed statistical research that shows the share of the specific variants in the regional variations of the Polish language, in several synchronic sectional views (vertical time segments). This research procedure will allow to show the source of new linguistic norms, the rate at which they disseminate and which regions are the most innovative ones.